Entomological surveillance of mosquitoes (Diptera: Culicidae), vectors of arboviruses, in an ecotourism park in Cachoeiras de Macacu, state of Rio de Janeiro-RJ, Brazil - Balthazar, Thamiris D’A.; Maia, Danielle A.; Oliveira, Alexandre A.; Marques, William A.; Bastos, Amanda Q.; Vilela, Mauricio L.; Mallet, Jacenir R. S. (PLOS ONE, 2021)
Arboviruses are arthropod-dependent viruses to complete their zoonotic cycle. Among the transmitting arthropods, culicids stand out, which participate in the cycle of several arboviruses that can affect humans. The present study aimed to identify species of culicidae and to point out the risk of circulation, emergency, or reemergence of pathogenic arboviruses to humans in the region of the Jequitibá headquarters of the Parque Estadual dos Três Picos (PETP), in Cachoeiras de Macacu, state of Rio de Janeiro, Brazil. Sampling was carried out at five Sample Points (SP) demarcated on trails from the headquarters, with CDC light traps, HP model with dry ice attached to the side, for 48 hours of activity each month. Additionally, active catches were made with a castro catcher in the period of one hour per day in the field, from six to eleven o’clock in the morning, in each PM. After the captures, thematic map was assembled using the ArcGIS 10 software and performing a multidimensional scaling (MDS). A total of 1151 specimens were captured and the presence of culicids already incriminated as vectors of arboviruses circulating in the region was observed: Aedes fluviatilis Lutz, 1904 (71 specimens); Aedes scapularis Rondani, 1848 (55 specimens); Haemagogus leococelaenus Dyar and Shannon, 1924 (29 specimens). In addition to the subgenus Culex (culex) spp. (163 specimens). In this sense, we highlight the importance of strengthening the actions of continuous entomological surveillance of the emergence and re-emergence of new arboviruses in ecotourism visitation parks.